Titanium dioxide nanoparticles exacerbate DSS-induced colitis: role of the NLRP3 inflammasome. Issue 7 (4th February 2016) - Ruiz, Pedro A; Morón, Belen; Becker, Helen M; Lang, Silvia; Atrott, Kirstin; Spalinger, Marianne R; Scharl, Michael; Wojtal, Kacper A; Fischbeck-Terhalle, Anne; Frey-Wagner, Isabelle; Hausmann, Martin; Kraemer, Thomas; et al.
Abstract : Objective: Western lifestyle and diet are major environmental factors playing a role in the development of IBD. Titanium dioxide (TiO2 ) nanoparticles are widely used as food additives or in pharmaceutical formulations and are consumed by millions of people on a daily basis. We investigated the effects of TiO2 in the development of colitis and the role of the nucleotide-binding oligomerisation domain receptor, pyrin domain containing (NLRP)3 inflammasome. Design: Wild-type and NLRP3-deficient mice with dextran sodium sulfate-induced colitis were orally administered with TiO2 nanoparticles. The proinflammatory effects of TiO2 particles in cultured human intestinal epithelial cells (IECs) and macrophages were also studied, as well as the ability of TiO2 crystals to traverse IEC monolayers and accumulate in the blood of patients with IBD using inductively coupled plasma mass spectrometry. Results: Oral administration of TiO2 nanoparticles worsened acute colitis through a mechanism involving the NLRP3 inflammasome. Importantly, crystals were found to accumulate in spleen of TiO2 -administered mice. In vitro, TiO2 particles were taken up by IECs and macrophages and triggered NLRP3-ASC-caspase-1 assembly, caspase-1 cleavage and the release of NLRP3-associated interleukin (IL)-1β and IL-18. TiO2 also induced reactive oxygen species generation and increased epithelial permeability in IEC monolayers. Increased levels of titanium were found in blood of patients with UC having active disease. Conclusion: These findings indicate that individuals with a defective intestinal barrier function and pre-existing inflammatory condition, such as IBD, might be negatively impacted by the use of TiO2 nanoparticles.